Progression of nailfold capillaroscopic patterns and correlation with organ involvement in systemic sclerosis: a 12 year study. (17th September 2019) - Sulli, A; Paolino, S; Pizzorni, C; Ferrari, G; Pacini, G; Pesce, G; Carmisciano, L; Smith, V; Cutolo, M
Abstract: Objective: The aim of this observational study was to investigate the evolution of scleroderma microangiopathy throughout different nailfold videocapillaroscopy (NVC) patterns ('early', 'active', 'late') as well as the prevalence of organ involvement in SSc patients during a 12-year follow-up. Methods: Thirty-four SSc patients showing at baseline (first capillaroscopic analysis) the 'early' NVC pattern of microangiopathy were enrolled and followed for 12 years (s .d . 2). Complete NVC analysis and clinical and serological findings were collected. Patients were in a standard therapeutic care setting. Statistical analysis was carried out by non-parametric tests. Results: After a 12-year follow-up, the 'early' NVC pattern changed from baseline in 76% of the patients. The NVC pattern was found to be 'active' in 9 patients (26%), 'late' in 13 (38%) and characterized by non-specific capillary abnormalities in 4 (12%). In the subgroup whose microangiopathy progressed from the 'early' to the 'late' NVC pattern, the median time of progression from the 'early' to the 'active' pattern was significantly shorter (11 months) when compared with patients who progressed from the 'early' to the 'active' NVC pattern (55 months) ( P = 0.002). The median time of progression between NVC patterns was significantly shorter in SSc patients showing either a nucleolar ANA pattern or Scl70 autoantibodies ( P = 0.048). Organ involvement was progressively greater in SSc patients with 'early', 'active' and 'late' NVC patterns, respectively. Conclusions: This longitudinal study confirms over a 12-year follow-up the evolution of specific NVC patterns associated with the progressive severity of organ involvement in SSc patients in a standard clinical care setting.